Strategi Kolaborasi Pemerintah dan Perusahaan dalam Meningkatkan Efektivitas Pengelolaan Bisnis dan Kepatuhan Hukum di Indonesia - Prayitno, Arief (Faculty of Law, Universitas Pekalongan, 2024)
Effective business management and legal compliance are essential to create corporate stability and competitiveness, especially in Indonesia which has complex regulations. Compliance with the law helps companies build reputation, reduce risks and contribute to sustainable economic development. Collaboration between government and companies is key to creating a healthy business ecosystem, supporting economic growth, and ensuring transparency and accountability in business practices. This study aims to analyze the collaboration strategy between government and companies in improving the effectiveness of business management and legal compliance in Indonesia. This study uses a normative legal approach that relies on tracing applicable laws and other complementary sources. The results of the study indicate that collaboration between the government and companies in improving the effectiveness of business management and legal compliance is very important to create a transparent, efficient, and sustainable business environment. With the role of the government in providing regulations that support operational efficiency, incentives for law-abiding companies, and the provision of skills-based training, companies can operate better and comply with legal obligations. In addition, the use of technology and digitalization of legal administration processes can improve efficiency and transparency, while synergies in corporate social responsibility (CSR) programs and awards for law-abiding companies help strengthen the culture of compliance. All of this creates a business ecosystem that not only benefits companies, but also contributes to economic development and community welfare